KEMAMPUAN PEMECAHAN MASALAH MATEMATIS MELALUI PROBLEM BASED LEARNING - Octaria, Dina; Puspa Sari, Eka Fitri (Jurnal Dosen Universitas PGRI Palembang)
ABSTRACTThis study aims to determine the ability of mathematical problem solving (KPMM) of students through the model of learning problem based learning (PBL). This study used quasi-experimental method with the control group design of pretest and non-equivalent postes. The subject of this research is the fourth semester student of the academic year 2016/2017 at the mathematics education program at PGRI University of Palembang which amounted to 62 people. Based on the learning, the research subjects are divided into two classes, namely the experimental class that get the PBL learning and control class that get conventional learning (PK). Instruments in this study using KPMM test. The data in this study were analyzed using t-test. From the data analysis, it is found that students mathematical problem solving ability through PBL learning is better than those who get conventionallearning in terms of overall or KAM (high, medium, low).Keywords: problem based learning (PBL), problem-solving ability